Implementation of Strengthening the Pancasila Student Profile Independent Curriculum As A Strengthening of Independent and Creative Character in Elementary Schools - Dewi Herlisti , Risma (International Proceedings of Nusantara Raya, 2024)
This research aims to examine the implementation of strengthening the Pancasila Student profile in the Independent Curriculum, especially in the context of developing independent and creative character in elementary school students. Using a qualitative approach, this research involved participatory observation, in-depth interviews with teachers, students and school principals, as well as analysis of learning documents. The research results show that the Merdeka Curriculum provides flexibility for teachers to design student-centered and project-oriented learning. The stages start from understanding the profile strengthening project, preparing the school ecosystem, designing the Pancasila student profile strengthening project, managing the assessment and reporting the Pancasila student profile strengthening project, to the evaluation and follow-up of the Pancasila student profile strengthening project.This approach encourages students to actively seek information, solve problems, and produce original work, so as to improve their independent and creative character. However, this research also identified several challenges in implementation, such as a lack of adequate resources, as well as the need to develop teacher capacity in designing innovative learning. The implication of this research is the importance of providing ongoing training for teachers in implementing the Independent Curriculum, as well as providing supporting resources to create a learning environment that is conducive to student character development. It is hoped that the research results obtained will be beneficial for further research